Adolescents’ Gender And Age As Correlates Of Career Choice Among Secondary School Students In Southwest Nigeria - Joseph, FABUNMI; Julius O., ADEDAYO (Advances in Social Sciences Research Journal, 2017)
The issues of gender and adolescents age difference as they relate with choice of career among secondary school students in southwest Nigeria are the core concerns of this paper. The study was an empirical one which focused on senior secondary school students who are in their penultimate years in the secondary school, where subject selection takes place based on their career interests. A total of 100 SSII students responded to the study, who were selected through a multistage random sampling technique. The instrument, tagged “Student Career Inventory (SCI) was constructed by the researchers and validated against two similar instruments namely - the Vocational Interest Inventory (VII) and Career Inventory Survey (CIS) for content and construct validities using factor analysis. This yielded coefficients of 0.58 and 0.63 respectively. The same process of factor analysis was used to test the reliability of the instrument which was found to be reliable with a coefficient of 0.966. The finding of the study showed a significance difference in the choice of career between male and female students, but not significant as with respect to age difference between 15 and 17 years. Based on this, it was recommended among others that gender issue should be put into consideration when career choice is to be treated.